Contribution of gender towards open source software: A preliminary study - Mahmod, Musyrifah; Md Dahalin, Zulkhairi; Abdul Hamid, Norsiah; Ahmad, Azizah (2012)
Open Source Software(OSS)innovation process has become a prominent phenomenon on how software is developed.Yet, gender issues in software industry seem to be duplicated in OSS innovation process.This paper discusses preliminary findings to address the lacuna in the area of OSS innovation process and gender.The study is guided by Social Construction of Technology (SCOT) theory and Feminist theory.This study offer insights for OSS community, not only the benefit towards gender and minorities but familiarizing them with the dynamics, issues and challenges related to OSS innovation thus enhanced their understanding of gender’s and minorities’ contribution in OSS innovation.